Efectto del pH y de la luz sobre la biologia de Sclerotium rolfsii Sacc - Camara, M.=700 1 Herrera, I.L.; Galantai, E.
(En, Es)
Ilus., 9 ref.
Keywords: BIOLOGIA; CORTICIUM ROLFSII; PH; LUZ; HONGOS; CUBA